Community Biodiversity Management: Promoting resilience and the conservation of plant genetic resources - Simon de Boef, W.; Subedi, A.; Peroni, N.; Thijssen, Marja H.; O'Keeffe, E. (Routledge, 2013)
This book sets out a clear overview of Community Biodiversity Management (CBM) as a methodology for meeting socio-environmental changes. The authors present the underlying concepts and theories of CBM as well as its methodology and practices, using case studies primarily from Brazil, Ethiopia, France, India, and Nepal.